Crack propagation in an energy storage flywheel rotor using finite element method - Ailene B. Nuñez; Aristotle T. Ubando; Jeremias A. Gonzaga; Roy Francis R. Navea; Gil Nonato C. Santos; Wei-Hsin Chen (Results in Engineering)
This study presents a simulation-based approach to evaluate crack initiation and propagation in steel flywheel energy storage rotors under centrifugal loading. A high-fidelity finite element model was constructed and validated against benchmark stress profiles, with the area under the curve deviations below 2 % and statistical confirmation via paired T-test (p = 0.2575). Stress concentration was observed at the rotor-shaft junction, indicating it as a primary crack initiation zone. A parametric model fitted to simulation data approximated J-integral values with R² = 0.95 and a mean absolute error of 2.47 %, capturing dominant trends across the design space. Separately, a Gaussian Process Prediction Model (GPPM), trained on a Gaussian Process-based space-filling design (GPM-SFD), achieved R² = 1.0 on training data and 0.936 on test data, demonstrating strong predictive generalization and stability. The highest energy release rate (684.84 J/m²) occurred for a 20 mm radial crack near the shaft at 10,000 rpm, marking the most fracture-prone configuration. Crack propagation simulations revealed pure mode I dominance (> 99.99 %) in radial cracks and mixed-mode behavior in tangential cracks, with mode II reaching 1.2 % and mode III exhibiting antisymmetric torsion. These results establish critical thresholds for crack growth, inform fatigue failure predictions, and support digital twin deployment for real-time structural monitoring in high-speed rotating systems.